Mechanisms of action and in vivo antibacterial efficacy assessment of five novel hybrid peptides derived from Indolicidin and Ranalexin against Streptococcus pneumoniae - Jindal, H.M.; Zandi, K.; Ong, Kien Chai; Velayuthan, Rukumani Devi; Rasid, S.M.; Samudi, Chandramathi; Sekaran, Shamala Devi (PeerJ, 2017)
Background. Antimicrobial peptides (AMPs) are of great potential as novel antibiotics for the treatment of broad spectrum of pathogenic microorganisms including resistant bacteria. In this study, the mechanisms of action and the therapeutic efficacy of the hybrid peptides were examined. Methods. TEM, SEM and ATP efflux assay were used to evaluate the effect of hybrid peptides on the integrity of the pneumococcal cell wall/membrane. DNA retardation assay was assessed to measure the impact of hybrid peptides on the migration of genomic DNA through the agarose gel. In vitro synergistic effect was checked using the chequerboard assay. ICR male mice were used to evaluate the in vivo toxicity and antibacterial activity of the hybrid peptides in a standalone form and in combination with ceftriaxone. Results. The results obtained from TEM and SEM indicated that the hybrid pep- tides caused significant morphological alterations in Streptococcus pneumoniae and disrupting the integrity of the cell wall/membrane. The rapid release of ATP from pneumococcal cells after one hour of incubation proposing that the antibacterial action for the hybrid peptides is based on membrane permeabilization and damage. The DNA retardation assay revealed that at 62.5 μg/ml all the hybrid peptides were capable of binding and preventing the pneumococcal genomic DNA from migrating through the agarose gel. In vitro synergy was observed when pneumococcal cells treated with combinations of hybrid peptides with each other and with conventional drugs erythromycin and ceftriaxone. The in vivo therapeutic efficacy results revealed that the hybrid peptide RN7-IN8 at 20 mg/kg could improve the survival rate of pneumococcal bacteremia infected mice, as 50% of the infected mice survived up to seven days post- infection. In vivo antibacterial efficacy of the hybrid peptide RN7-IN8 was signficantly improved when combined with the standard antibiotic ceftriaxone at (20 mg/kg + 20 mg/kg) as 100% of the infected mice survived up to seven days post-infection. Discussion. Our results suggest that attacking and breaching the cell wall/membrane is most probably the principal mechanism for the hybrid peptides. In addition, the hybrid peptides could possess another mechanism of action by inhibiting intracellular functions such as DNA synthesis. AMPs could play a great role in combating antibiotic resistance as they can reduce the therapeutic concentrations of standard drugs.